The Infertility problems HS Effects on human development (Journal of the College of Education for Women, 2019)
The problem of infertility considers one of the chronic problem a which faced theindividual & families equally . This problem causes a negative effects in psychological ,social and development fields. The infertility contributes in weakening the humandevelopment, when the human development has become as a centre point which centeredabout individual preparing , rehabilitation, training and knowledge toreach to the requiredexcellence.We think that , the infertility destroys the socially development; therefore the socially andscientific institutions are working hard to find successful solution to resolve the probleminfertility through sophisticated and scientific methods. This problem faces the human beingmay be caused to woman by Biological failure or for psychological and social resons , as wellas the man for the same resons. The scientific studies proved that , there are some solution areavailable for women infertility while unavailable for meninfertility . This research has aimedto identify the causes and effects .The first subject has studied the scientific concepts whilethe second subject has studied the topic of marriage and reproduction . then studied the humandevelopment and its effects on the communities .There are two topics which are devoted for the applies side by create a form which is appliedto a sample of (100) clients of (males and females) were taken from three different places as(the Higher Institute of Infetility Diagnosis & the Assisted techniques for the reprouduction /Al- Nahrain University , Kama; Al- Samarrai Hospital for Infertility treatment and Zeenat Al—Hayat centre for Infertility treatment and IVF). The research is found to many results ,the most impotant one is that the causes of the infertility are resulted from some diseasessuch as (psychic shock, disorder in sexual and environmental pollution).The research finds a set of recommendations and proposals which we can contribute infinding suitable solutions this problem.